(untitled) (Konferensiyalar | Conferences, 2024)
This article is about intercultural competence which is very necessary, especially, in today`s world as people are travelling a lot for different purposes and communicating with individuals from different cultural backgrounds. Moreover, information is given to develop crosscultural understanding and skills of communication in the content of modern education.